Modular Assembly Systems: Benefits, challenges, Opportunities, Case studies and Best Practices - Savio, Rajesh Dominic (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
Modular assembly systems are a new way to meet urgent challenges that come with a highly dynamic world of global manufacturing for increased efficiency and flexibility in changing structures and sustainability. This paper outlines the challenges and potential solutions from modular assembly systems with multiple benefits, difficulties, and opportunities in various industries, such as automotive, electronics, oil and gas industry. Manufacturers can reduce lead times and capital investments by orders of magnitude while simultaneously reducing the use of resources and product variety-that is, what can be achieved with modular systems. Modular systems are not free, though, of problems in integration complexity and supply chain bottlenecks. Using Marriott International’s innovative work on affordable housing with modular construction as an example, this paper shows best practices and the potential in modular systems pertaining to scalability and sustainability. Altogether, the findings of this paper underscore the strategic advantages that modular assembly systems have in allowing organizations to develop innovation and growth in a competitive marketplace.